Application of a microbial fuel cell-based biosensor for the energy-saving operation of macrophyte residues bioreactor with low concentration of dissolved organic carbon in effluents. (April 2019) - Wang, Chunliu; Yao, Zongbao; Bai, Leilei; Wang, Changhui; Jiang, Helong
Abstract: The increasing application of plant residues bioreactor for aquatic environment remediation may release numerous dissolved organic carbon (DOC) into aquatic ecosystems. In this study, a microbial fuel cell (MFC) sensor was integrated with a macrophyte residues bioreactor (MRBR) to provide an energy-saving way for reduction of DOC concentrations in the effluent. Through re-utilization of macrophyte residues as solid carbon source, DOC concentrations in the effluent of MRBR increased to the maximum on day 5 and then dropped down rapidly to a low value, while the ratio of bioavailable DOC decreased gradually. Interestingly, it was found that there existed a linear relationship between DOC concentrations in initial residue leachate and the voltage from MFC biosensor ( R 2 = 0.9852). Accordingly, aerobic biofilm through aeration were applied in the upper part of MRBR to enhance the degradation of DOC prior to discharge to aquatic systems, and aeration rate was adjusted based on MFC sensor signal. Further experiments demonstrated that when voltage decreased from 0.18 V to 0.09 V, a half of aeration rate (7.5 L min −1 ) could still lead to a high DOC degradation efficiency (above 50%) and a low DOC concentration (∼10 mg L −1 ) in the reactor effluent. Thus, the integrated MFC signal could be used to regulate the aeration rate in order to obtain a low DOC concentration in effluents under an energy-saving way. Highlights: Linear relationship between DOC concentration in leachate and MFC voltage existed. MFC was integrated with MRBR for monitoring DOC concentrations in effluent. Aeration could reduce DOC concentration in effluent of MRBR effectively. Energy consumption of MRBR would be reduced according to MFC voltage signal.